Nodal-to-nodeless superconducting order parameter in LaFeAs1−x P x O synthesized under high pressure - Toni Shiroka; Nicolò Barbero; Rustem Khasanov; Nikolai D. Zhigadlo; Hans Rudolf Ott; Joel Mesot (npj Quantum Materials, 2018)
Superconductivity: Putting the pressure on iron-based superconductors Experiments show how iron-based superconductors synthesized under high pressure differ from those grown under ambient conditions. Iron-based superconductors are an exciting family of materials that exhibit unconventional superconductivity as well as a range of other exotic phases due to a complex interplay between magnetism and superconductivity. Oxypnictides are particularly puzzling members of this family as seemingly similar compounds can exhibit strikingly different electronic properties. By growing and measuring a range of oxypnictide compounds grown under different high-pressure, high-temperature conditions a team of researchers from Switzerland, led by Toni Shiroka from ETH Zürich, show that a close interplay between the magnetism and superconductivity is meditated by spin fluctuations. Furthermore, they show that the superconducting order parameter evolves in a way that is completely opposite to ambient-grown samples.